2012
DOI: 10.1209/0295-5075/98/68002
|View full text |Cite
|
Sign up to set email alerts
|

Towards a temporal network analysis of interactive WiFi users

Abstract: Networks PACS 89.65.-s -Social and economic systemsRecently, the analysis of temporal features of complex communication networks, especially the human contact networks, have received a boost with the advance of information technology, e.g., wireless communication. Newly created digital instruments not only reshape our daily life, but also record tremendous digital data produced by human daily activities, which can be utilized to analyze human behaviors [17][18][19][20]. WiFi, as a ubiquitous wireless accessing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…The data analysis reveals an unexpected feature that the distribution of the number of distinct persons each individual encounters every day only has a small squared coefficient of variance [162,164,166,167,168,169], irrespective of the specific social contexts (see Fig. 10).…”
Section: Studies Using Digital Equipmentmentioning
confidence: 98%
See 1 more Smart Citation
“…The data analysis reveals an unexpected feature that the distribution of the number of distinct persons each individual encounters every day only has a small squared coefficient of variance [162,164,166,167,168,169], irrespective of the specific social contexts (see Fig. 10).…”
Section: Studies Using Digital Equipmentmentioning
confidence: 98%
“…[160,161] referred to the Bluetooth technique embedded in mobile phones, which collects the proxy data of person-to-person interactions of MIT Media Laboratory in the Reality Mining program; with the help of wireless sensors, the social experiment was conducted to trace the close proximity contacts among the members of an American high school [162]; Ref. [163,164,165,166] considered the active Radio Frequency Identification Devices (RFID) to establish a flexible platform recording the face-to-face proximity contacts among volunteers, which had been deployed in various social contexts such as conference, museum, hospital, and primary school; and the WiFi accessing data among all students and staffs were also analyzed as the indirect proxy records of their concurrent communications in one Chinese University [167,168]. Compared with the above-mentioned data of questionnaires, the electronic data generated by digital experiments is more accurate and objective.…”
Section: Studies Using Digital Equipmentmentioning
confidence: 99%
“…These networks include spatial network (whose nodes occupy a precise position in two or three-dimensional Euclidean space, and whose edges are real physical connections) [214][215][216][217], adaptive networks [218], temporal or time-varying networks [219][220][221] (for more details, please also see Section 11).…”
Section: Type Of Networkmentioning
confidence: 99%
“…It has been found that the scale-free networks [2226] might provide a unified platform to foster the cooperation for nearly all main social dilemmas, such as PDG, snowdrift game (SDG), public goods game (PGG) etc, and the evolutionary outcome is also very robust against the normalization of payoffs. Furthermore, the heterogeneity and diversity [2735], which is considered by the individual behavior as well as those concerned in terms of players having different degree within a network, has been proved to be a very effective manner to promote the cooperation, and indeed many co-evolutionary rules [3639] have also been introduced to spontaneously create the heterogeneous state so as to maintain the surprisingly high cooperation level (see [40] for a full review).…”
Section: Introductionmentioning
confidence: 99%